A closer look at medical affairs - Godinho, Pedro Francisco Soares da Silva Mendes (2015)
Over the last 10 years, the Pharmaceutical Industry has been under great scrutiny from regulators, healthcare professionals (HCPs) and patients in general, as in the past it was criticized for the use of aggressive sales and marketing tactics and unethical behaviour. To increase the transparency on the activities developed and its relationship with physicians, it has undergone significant changes in the way that it develops and markets medicines and medical devices. Many of these changes have led to an increase in the responsibility of Medical Affairs to inform the healthcare professionals’ community on the safe and appropriate use of the company´s medicines. Additionally, there is a trend to greatly limit physician access to traditional sales representatives who traditionally were industry’s vehicle of information and replace them by unbiased subject matter experts, the Medical Affairs colleagues. Much of this communication activity involves engaging and developing longterm relationships with key scientific opinion leaders in the disease area of interest. These scientific partnerships are crucial for the improvement of health outcomes that the pharmaceutical companies aim to achieve. The methods used by Medical Affairs to communicate the science vary from manuscripts in peer-reviewed journals, to congresses, continuous medical education meetings and discussion groups. More recently, digital channels have also been more frequently used to engage HCPs and even patients in this scientific exchange. Medical Affairs have significantly impacted the relationship with customers, continuing to build trust and value, transparency in all engagements, providing a balanced discussion of benefits and risks, and leveraging clinically robust dialogues on a peer-to-peer level. Medical Affairs activity, helping to address patients and physicians’ needs and promoting the appropriate use of medicines, will contribute to improve the reputation of the pharmaceutical industry.